The Role of Indonesian Doctors as Content Creators in Fighting Health Hoaxes, Myths, and Stigma on Social Media - Anjelia, Lydia Okva; Mulyana, Deddy; Suminar, Jenny Ratna (UI Scholars Hub, 2024)
Amidst the proliferation of disinformation and misinformation related to health on social media, the public must ensure that the sources of information are trustworthy. This research aims to explain the role of doctors in the fight against health hoaxes, myths, and stigma spread through social media. The study adopts qualitative research with a phenomenological approach to understand doctors' experiences and perceptions regarding their efforts to address health hoaxes, myths, and stigma on social media. Fifteen doctors as content creators in Jakarta and Bandung were selected as informants using purposive sampling. The data was collected through interviews, observation participation, and documentation studies. The study showed that doctors (1) have a significant role in the fight against health hoaxes, myths, and stigma on social media, consisting of doctors as sources of accurate information, educators, and public health advocacy; (2) use any feature tools on social media such as making Q&A, stitch some content hoaxes, myths, and stigma, and collaboration with another expert, government, agencies, or health organizations ; (3) provide accurate information based on the educational process and scientific evidence.